Artesunate, as an Hsp90 inhibitor, inhibits the proliferation of Burkitt’s lymphoma cells by inhibiting AKT and ERK - Yuan-Ce, Li; Qi, Zhang; Hong-Yang, Zhang; Yan-Wen, Wang; Yu-Mei, Sun; Bi-Juan, Yang; Jun-Lin, Yin (Frontiers in Pharmacology, 2023)
Abstract Artesunate, a derivative of artemisinin, has anti-malarial effects, and in recent years has also been reported to have anti-tumor activity. However, its anti-tumor mechanisms are not well understood. In this study, we focused on the targeting of Hsp90 by artesunate to inhibit tumor cell proliferation, which we examined using immunoprecipitation, a proliferation assay, flow cytometry, western blotting, a tumor xenograft animal model, and immunohistochemistry. Furthermore, to examine the tumor-suppressive effects of artesunate in nude mice, we used artesunate-loaded PLGA-PEG nanoparticles. The binding of artesunate to Hsp90 was found to reduce the expression of its client proteins AKT, ERK, p-AKT, p-ERK, and EGFR, thereby blocking the cell cycle at the G0/G1 → S stage in lymphoma cells and inducing apoptosis. In addition, the results of tumor xenograft experiments revealed that artesunate reduced the expression of AKT and ERK proteins in tumor tissues, inhibited tumor proliferation, and reduced tumor size and weight. Furthermore, nanoparticle encapsulation was demonstrated to enhance the anti-cancer activity of artesunate. We thus established that artesunate inhibits the proliferation of lymphoma cells by targeting the Hsp90 protein, and we accordingly believe that this compound has potential for development as a novel anti-tumor drug.